Effect of stroke etiology on endovascular thrombectomy with or without intravenous alteplase: a subgroup analysis of DIRECT-MT. (11th January 2022) - Xing, Pengfei; Zhang, Xiaoxi; Shen, Hongjian; Shen, Fang; Zhang, Lei; Li, Zifu; Zhang, Yongxin; Hong, Bo; Shi, Huaizhang; Han, Hongxing; Ye, Xiaofei; Zhang, Yongwei; et al.
Abstract : Background: Stroke etiology might influence the clinical outcomes in patients with large vessel occlusion receiving endovascular treatment (EVT) with or without thrombolysis. Objective: To examine whether stroke etiology resulted in different efficacy and safety in patients treated with EVT-alone or EVT preceded by intravenous alteplase (combined therapy). Methods: We assessed the efficacy and safety of treatment strategy based on prespecified stroke etiology, cardioembolism (CE), large-artery atherosclerosis (LAA), and undetermined cause (UC) for patients enrolled in the DIRECT-MT trial. The primary outcome was the modified Rankin Scale (mRS) score at 90 days. Multivariate ordinal logistic regression analysis was used to calculate the adjusted common OR for a shift of better mRS score for EVT-alone versus combined therapy. A term was entered to test for interaction. Results: In this study, 656 patients were grouped into three prespecified stroke etiologic subgroups. The adjusted common ORs for improvement in the 90-day ordinal mRS score with EVT-alone were 1.2 (95% CI 0.8 to 1.8) for CE, 1.6 (95% CI 0.8 to 3.3) for LAA, and 0.8 (95% CI 0.5 to 1.3) for UC. Compared with CE, EVT-alone was more likely to result in an mRS score of 0–1 (pinteraction =0.047) and extended Thrombolysis in Cerebral Infarction ≥2b (pinteraction =0.041) in the LAA group. The differences in mortality and symptomatic intracranial hemorrhage within 90 days were not significant between the subgroups (p＞0.05). Conclusions: The results did not support the hypothesis that a specific treatment strategy based on stroke etiology should be used for patients with large vessel occlusion (NCT03469206 ).